Library and Information Science through Distance Education - Sathyanarayana, R. (Journal of Information and Knowledge, 2014)
The concept of ’Distance Education’ is a relatively new one aimed at the expansion of education through the use of modern communications technology. Following the lead of the British Open University distance learing institutions have been established in many developed and developing countries of the world.